The Influence of Virtual Character Design on Emotional Engagement in Immersive Virtual Reality: The Case of Feelings of Being - Dirin, Amir; Laine, Teemu H. (Electronics (Switzerland), 2023)
Immersive virtual reality applications based on head-mounted displays are gaining momentum among students and educational institutes, but there is a lack of information about the preferences of virtual characters and emotional engagement in these applications. The objectives of this study were to: (i) evaluate participants’ preferences on virtual characters in virtual reality; (ii) measure emotional engagement among the users in terms of Feelings of Being; and (iii) identify relationships between virtual characters and emotional engagement. We conducted a mixed-method user experience evaluation on the HHVR virtual reality application that introduces the premises of a Finnish university and has three virtual characters: a human virtual character based on a real person, a fictional human virtual character, and a cat virtual character. We set up an eSports event where presenters (N = 12, mean age: 31.09) experienced HHVR using a head-mounted display and spectators (N = 38, mean age: 25.95) observed the experiment through large screens. We administered a questionnaire and conducted semi-structured interviews to gain insights into the participants’ preferences on virtual characters and emotional engagement. The results indicated that the virtual character preferences varied between the presenters and spectators; the cat was a highly liked virtual character in both groups, and the realistic human virtual character garnered mixed reactions from the spectators, although she was generally liked by the presenters. Both groups experienced several Feelings of Being, such as engagement, effectiveness, security, trust, enjoyment, and excitement, during the HHVR experience. Moderate and significant correlations were identified between the virtual characters and some of the Feelings of Being, thus indicating that the type of virtual character could impact emotional engagement; however, this requires further exploration.
Keywords: emotional engagement; feelings of being; user experience; virtual character; virtual reality